Studi Ekonomi Lingkungan Penggunaan Pestisida dan Dampaknya Pada Kesehatan Petani di Area Pertanian Hortikultura Desa Sumber Rejo Kecamatan Ngablak Kabupaten Magelang - Yuantari, MG Catur; Setiani, Onny; Nurjazuli, Nurjazuli (Jurnal Kesehatan Lingkungan Indonesia, 2009)
ABSTRACT Background: Pesticides using in the agricultural system has a role in increasing the plant production, however, pesticides are also hazardous materials that could cause a negative human health effect and environmental sustainability. Based on the results of blood examination of cholinesterase on farmers in Magelang regency in 2006 with the number of examined samples of 550 people showed that 99.8% of them were poisoned. They consisted of 18.2% severe poisoning 72.73% moderate poisoning; and 8.9% mild poisoning. This research aimed to explore the impact of environmental economic resulting from the use of pesticides on the farmers’s health in the horticulture farming area in Sumber Rejo village, Ngablak Sub District, Magelang District. Method: It was an observation research using a cross-sectional approach. The population was all farmers of vegetable at Sumber rejo village, Sub District of Ngablak. Sixty eight samples were taken using the simple random sanpling, while the 20 residues of pesticides in soil samples were taken for laboratory examination. Data were analyzed using Chi-Square and regression logistic test. Result: The result of this research showed a significant relationship between the dose of pesticide using (p= 0,001), the use of self protective equipment or SPE (p = 0,001), method of spraying (p= 0,001), the method of mixing (p = 0,032) and mixing location (p = 0,002) with the incidende of organofosfat pesticides poisoning. Conclusions: Based on cholinesterase examination on farmers of vegetable who suffered pesticide poisoning were 76,5 %, it needs more attention from the government to control the pesticide poisoning on farmers. Keywords: Environmental Economic, using pesticide, farmers of horticulture.